Inter subject variability and reproducibility of diffusion tensor imaging within and between different imaging sessions. - Tonny V Veenith; Eleanor Carter; Julia Grossac; Virginia F J Newcombe; Joanne G Outtrim; Victoria Lupson; Guy B Williams; David K Menon; Jonathan P Coles (PLoS ONE)
The aim of these studies was to provide reference data on intersubject variability and reproducibility of diffusion tensor imaging. Healthy volunteers underwent imaging on two occasions using the same 3T Siemens Verio magnetic resonance scanner. At each session two identical diffusion tensor sequences were obtained along with standard structural imaging. Fractional anisotropy, apparent diffusion coefficient, axial and radial diffusivity maps were created and regions of interest applied in normalised space. The baseline data from all 26 volunteers were used to calculate the intersubject variability, while within session and between session reproducibility were calculated from all the available data. The reproducibility of measurements were used to calculate the overall and within session 95% prediction interval for zero change. The within and between session reproducibility data were lower than the values for intersubject variability, and were different across the brain. The regional mean (range) coefficient of variation figures for within session reproducibility were 2.1 (0.9-5.5%), 1.2 (0.4-3.9%), 1.2 (0.4-3.8%) and 1.8 (0.4-4.3%) for fractional anisotropy, apparent diffusion coefficient, axial and radial diffusivity, and were lower than between session reproducibility measurements (2.4 (1.1-5.9%), 1.9 (0.7-5.7%), 1.7 (0.7-4.7%) and 2.4 (0.9-5.8%); p<0.001). The calculated overall and within session 95% prediction intervals for zero change were similar. This study provides additional reference data concerning intersubject variability and reproducibility of diffusion tensor imaging conducted within the same imaging session and different imaging sessions. These data can be utilised in interventional studies to quantify change within a single imaging session, or to assess the significance of change in longitudinal studies of brain injury and disease.